From single-particle excitations to sound waves in a box-trapped atomic Bose-Einstein condensate - Garratt, S; Eigen, C; Zhang, J; Turzák, P; Lopes, R; Smith, R; Hadzibabic, Z; Navon, N (American Physical Society, 2019)
We experimentally and theoretically investigate the lowest-lying axial excitation of an atomic Bose-Einstein condensate in a cylindrical box trap. By tuning the atomic density, we observe how the nature of the mode changes from a single-particle excitation (in the low-density limit) to a sound wave (in the high-density limit). We elucidate the physics of the crossover between the two limiting regimes using Bogoliubov theory, and find excellent agreement with the measurements. Finally, for large excitation amplitudes we observe a non-exponential decay of the mode, suggesting a nonlinear many-body decay mechanism.